Children's Perspective on Social Workers' Questioning Practices - Sørensen, Kresta Munkholt; Jacobsen, Charlotte Bredahl; Koustrup, Cecilie (Child & family social work, 2024)
Three tendencies currently influence social workers' questioning practices at statutory meetings with children in out‐of‐home care: an awareness that the children may have unmet needs that social workers should detect and react upon the introduction of screening instruments to social work and changes in questioning practices due to a quest for greater child participation. This project explores children's preferences about social workers' questioning practices given these trends . A total of 18 Danish children aged 10–13 participated in three separate panels in 2020 and 2021. Each panel met up on three Saturday afternoons to discuss and offer opinions on subjects that included social workers' questioning practices with or without the use of screening questionnaires. According to the children, social workers need to reach a better balance between children's right to privacy and their need for help. They want fewer people ‘meddling in their lives’, more privacy and to be questioned only when social workers can act very concretely to help them solve a problem. Children's preferences indicate that we should adjust social work questioning practices with children placed in out‐of‐home care in general and our use of screening instruments in social work in particular.